The holistic way of tackling the COVID-19 pandemic: the one health approach - Vivian Mushi (Tropical Medicine and Health, 2020)
Abstract The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that is causing a global pandemic had a zoonotic origin in China. Considering the inter-connectedness between human, environment, and animal health, the One Health approach is the appropriate strategy to control and mitigate the effects of the ongoing coronavirus disease 2019 (COVID-19). This letter explains the benefits of the One Health approach and recommends specific measures that could be taken to accelerate the fight against COVID-19 and prevent the spread of newly emerging infectious diseases.